2011
DOI: 10.1016/j.tem.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue: emerging physiological, pathophysiological and clinical features

Abstract: Epicardial adipose tissue is an unusual visceral fat depot with anatomical and functional contiguity to the myocardium and coronary arteries. Under physiological conditions, epicardial adipose tissue displays biochemical, mechanical and thermogenic cardioprotective properties. Under pathological circumstances, epicardial fat can locally affect the heart and coronary arteries through vasocrine or paracrine secretion of proinflammatory cytokines. What influences this equilibrium remains unclear. Improved local v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
425
1
33

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(468 citation statements)
references
References 87 publications
9
425
1
33
Order By: Relevance
“…In the last years growing evidence also suggests that the increase in epicardial fat can be considered a cardiometabolic risk factor [32], being associated with the metabolic syndrome [33], with a diagnosis of NAFLD both by US or MR spectroscopy [14][15][16][17][18], with carotid atherosclerosis [34] and coronary artery disease [35]. Accordingly, we confirmed the association of epicardial fat thickness with older age, visceral obesity, hypertension and statin use, well-known factors associated with an increased cardiovascular risk.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the last years growing evidence also suggests that the increase in epicardial fat can be considered a cardiometabolic risk factor [32], being associated with the metabolic syndrome [33], with a diagnosis of NAFLD both by US or MR spectroscopy [14][15][16][17][18], with carotid atherosclerosis [34] and coronary artery disease [35]. Accordingly, we confirmed the association of epicardial fat thickness with older age, visceral obesity, hypertension and statin use, well-known factors associated with an increased cardiovascular risk.…”
Section: Discussionsupporting
confidence: 83%
“…However, we may put forward a few hypotheses, leaving the demonstration of pathophysiological mechanisms to experimental studies. First, increased epicardial fat is able to act as a paracrince/endocrine organ and to secrete proatherogenic and proinflammatory adipokines, as tumor necrosis factor alfa, interleukin 6, interleukin 1beta and angiotensin [32]. In turn, these chemokines may activate stellate cells, leading to liver fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…20 In terms of its distribution, postmortem studies have revealed that epicardial fat can cover up to 80% of the heart surface and contribute up to 20% of total ventricular weight under normal conditions, while being capable of covering the heart completely and even extending up to 2 cm in thickness during obesity in humans. 21,22 Anatomically, epicardial fat is not separated from the underlying myocardium with any fascia-like structure and is also known to share coronary blood supply with the latter, thereby supporting the idea of plausible 'vasocrine' or 'paracrine' cross talk between the two. However, a direct microcirculatory interconnection between the two has not been established so far.…”
Section: Physiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
“…Considering that fatty acids are the major source of fuel for contracting heart muscle, this proposal is highly plausible and therefore widely accepted. 8,22,27 However, it is important to note that these observations have not been repeated in other animal models or validated for human epicardial fat. Considering that rodents do not necessarily possess epicardial fat under normal conditions and even when observed (that is, due to obesity or aging), such as in the case of guinea pigs, epicardial fat distribution differs from that in humans.…”
Section: Physiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
See 1 more Smart Citation